ANALISIS MUTU MIE KERING HITAM BERBAHAN TEPUNG CAMPURAN TERIGU-MOCAF DENGAN VARIASI PENAMBAHAN CARBON BLACK (Vegetable carbon) DARI DAUN PISANG KERING - Herlina, Herlina; Nurhayati, Nurhayati; Ramadhanni, Muhammad Badar (Jurnal Penelitian Sains dan Teknologi Indonesia, 2022)
This study aims to determine the effect of variations in the percentage addition of carbon black from dried banana leaves in the manufacture of dry noodles made from wheat-mocaf mixed flour on the physical, chemical and organoleptic properties and to determine the exact percentage of carbon black so as to produce dry noodles with good characteristics and preferred. The research design used a completely randomized design (CRD) with a single treatment with the percentage of addition of carbon black in the manufacture of dry noodles. The ratio of flour-mocaf mixture used in this study was 60:40 and the percentage of carbon black added to the mixed flour was (1, 2, 3, 4, and 5%). Each treatment was repeated 4 times. The test parameters in this study were physical parameters (color brightness, elasticity, water absorption, and cooking loss), chemical parameters (moisture content and ash content), sensory parameters (color, aroma, taste, elasticity, and overall). Based on the research results, it is known that the best formulation is dry noodles with mocaf substitution and the addition of carbon black, namely 5 grams of carbon black and 95 grams of mixed flour. Dry noodles with this treatment had an average elasticity value of 37.78 gr/mm, water absorption capacity of 2.34 gr/ml, cooking loss of 2.24 gr, water content of 8.72%, ash content of 3.88 gr.